Virucidal Activity of Fogged Chlorine Dioxide- and Hydrogen Peroxide-Based Disinfectants against Human Norovirus and Its Surrogate, Feline Calicivirus, on Hard-to-Reach Surfaces - Montazeri, Naim; Manuel, Clyde; Moorman, Eric; Khatiwada, Janak R.; Williams, Leonard L.; Jaykus, Lee-Ann (Frontiers in Microbiology, 2017)
Human norovirus (NoV) is the leading cause of foodborne illnesses in the United States. Norovirus is shed in high numbers in the feces and vomitous of infected individuals. Contact surfaces contaminated with bodily fluids harboring infectious virus particles serve as vehicles for pathogen transmission. Environmental stability of NoV and its resistance to many conventional disinfectants necessitate effective inactivation strategies to control the spread of virus. We investigated the efficacy of two commercial disinfectants, hydrogen peroxide (7.5%) and a chlorine dioxide (0.2%)-surfactant-based product using a fogging delivery system against human NoV GI.6 and GII.4 Sydney strains as well as the cultivable surrogate, feline calicivirus (FCV) dried on stainless steel coupons. Log10 reductions in human NoV and FCV were calculated utilizing RNase RT-qPCR and infectivity (plaque) assay, respectively. An improved antiviral activity of hydrogen peroxide as a function of disinfectant formulation concentration in the atmosphere was observed against both GII.4 and FCV. At 12.4 ml/m3, hydrogen peroxide achieved a respective 2.5±0.1 and 2.7±0.3 log10 reduction in GI.6 and GII.4 NoV genome copies, and a 4.3±0.1 log10 reduction in infectious FCV within 5 min. At the same disinfectant formulation concentration, chlorine dioxide-surfactant-based product resulted in a respective 1.7±0.2, 0.6±0.0 and 2.4±0.2 log10 reduction in GI.6, GII.4 and FCV within 10 min; however, increasing the disinfectant formulation concentration to 15.9 ml/m3 negatively impacted its efficacy. Fogging uniformly delivered the disinfectants throughout the room, and effectively decontaminated viruses on hard-to-reach surfaces. Hydrogen peroxide delivered by fog showed promising virucidal activity against FCV by meeting the U.S. EPA 4-log10 reduction criteria for an anti-noroviral disinfectant; however, fogged chlorine dioxide-surfactant-based product did not achieve a 4-log10 inactivation. Future investigation aimed at optimizing decontamination practices is warranted.